Antenatal Atazanavir: A Retrospective Analysis of Pregnancies Exposed to Atazanavir. (25th September 2014) - Samuel, Miriam; Bradshaw, Daniel; Perry, Melissa; Chan, Sum Yee; Dhairyawan, Rageshri; Byrne, Laura; Smith, Katherine; Zhou, Judith; Short, Charlotte Eve; Naftalin, Claire; Offodile, Ngozi; Mandalia, Sundhiya; et al.
Abstract : Introduction. There are few data regarding the tolerability, safety, or efficacy of antenatal atazanavir. We report our clinical experience of atazanavir use in pregnancy. Methods. A retrospective medical records review of atazanavir-exposed pregnancies in 12 London centres between 2004 and 2010. Results. There were 145 pregnancies in 135 women: 89 conceived whilst taking atazanavir-based combination antiretroviral therapy (cART), "preconception" atazanavir exposure; 27 started atazanavir-based cART as "first-line" during the pregnancy; and 29 "switched" to an atazanavir-based regimen from another cART regimen during pregnancy. Gastrointestinal intolerance requiring atazanavir cessation occurred in five pregnancies. Self-limiting, new-onset transaminitis was most common in first-line use, occurring in 11.0%. Atazanavir was commenced in five switch pregnancies in the presence of transaminitis, two of which discontinued atazanavir with persistent transaminitis. HIV-VL < 50 copies/mL was achieved in 89.3% preconception, 56.5% first-line, and 72.0% switch exposures. Singleton preterm delivery (<37 weeks) occurred in 11.7% preconception, 9.1% first-line, and 7.7% switch exposures. Four infants required phototherapy. There was one mother-to-child transmission in a poorly adherent woman. Conclusions. These data suggest that atazanavir is well tolerated and can be safely prescribed as a component of combination antiretroviral therapy in pregnancy.